ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS TERHADAP SOAL-SOAL OPEN ENDED - Nopitasari, Dian (Universitas Wiralodra, 2017)
The purpose of this study is to determine the level of students' mathematical creative thinking ability in solving open-ended problems in discrete mathematics courses. This research uses descriptive qualitative method. The population in this research is the third semester students of Mathematics Education UMT. The sample was taken by norm referenced evaluation technique that is students in semester III-A3 who have high, medium and low mathematical ability. The instruments used include creative thinking ability tests, observation sheets and interview guides. The result of data analysis shows that the students with the category of creative mathematical thinking level with the percentage of respondents is 84.61%, the category of mathematical creative thinking level is very low with 12.82% percentage, the level of creative creativity level is not creative with 2.56% percentage. From the result, we get the average category of students' mathematical creative thinking ability in the third semester-A3 is 67,94 with medium category level.